Differential diagnostic ultrasound criteria of papillary and follicular carcinomas: a multivariate analysis - Cordes, M.; Kondrat, P.; Uder, Michael; Kuwert, Torsten; Sasiadek, M. (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
The purpose of the study was to test the hypothesis that papillary thyroid carcinomas (PTCs) and follicular thyroid carcinomas (FTCs) appear with different ultrasound characteristics.90 patients (70 females, 20 males) were included in the study in whom after thyroidectomy the diagnoses of PTCs or FTCs were established. 33 patients (25 females, 8 males) with the diagnosis of follicular adenoma were included in the study as controls (KONs). All patients had ultrasound examinations of the thyroid preoperatively. These ultrasound examinations were evaluated retrospectively with respect to the ultrasound characteristics: "size", "shape", "contour", "structure", "echogenicity" and "calcifications".In PTCs, FTCs and KONs "size" was significantly different (PTCs: MW = 12.5 mm, SD = 8. mm - FTCs: MW = 35.4 mm, SD = 19.6 mm - KONs: MW = 22.7 mm, SD = 14.5 mm; p < 0.001 for PTCs vs. FTCs, p < 0.001 for PTCs vs. KONs, p = 0.013 for FTCs vs. KONs). Differences were also found with respect to "contour" and "echogenicity" among PTCs, FTCs and KONs (p <= 0.035). The parameters "size", "contour", "echogenicity" and "calcifications" correlated for PTCs, FTCs and KONs with a correlation coefficient r = 0.57 (p < 0.05, multivariate regressionanalysis).PTCs and FTCs appear with different sonographic characteristics. Although there is some overlapping of the sonographic appearances of PTCs and FTCs, the knowledge of these differences should have some impact of the risk adapted further work up.
EVALuna2:13825